2009
DOI: 10.1055/s-0029-1238214
|View full text |Cite
|
Sign up to set email alerts
|

Light at the End of the Tunnel: The Learning Curve Associated with Endoscopic Transsphenoidal Skull Base Surgery

Abstract: Endoscopic transsphenoidal resection of skull base lesions has been introduced widely as an alternative to microscopic transmucosal approaches. We report the introduction of this technique to our unit, including the learning curve recognized for this procedure, comparing techniques in a concurrent case-control fashion. All patients operated on for sellar, suprasellar, or clival lesions were considered for endoscopic surgery, with 51 patients undergoing endoscopic surgery and 46 having microscopic surgery with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 24 publications
2
43
0
5
Order By: Relevance
“…Prior studies evaluating the learning curve in endoscopic endonasal pituitary surgery have yielded mixed results. Sonnenburg et al evaluated their results with pi- 30 Another study demonstrated significant improvement in visual outcome and operating time after 50 endoscopic endonasal pituitary cases. 18 It would seem self-evident that there would be a learning curve in expanded endonasal cranial base procedures in which the depth of surgical field is increased and the lesions are more intimately associated with critical neurovascular structures.…”
Section: Learning Curve In Craniopharyngioma Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies evaluating the learning curve in endoscopic endonasal pituitary surgery have yielded mixed results. Sonnenburg et al evaluated their results with pi- 30 Another study demonstrated significant improvement in visual outcome and operating time after 50 endoscopic endonasal pituitary cases. 18 It would seem self-evident that there would be a learning curve in expanded endonasal cranial base procedures in which the depth of surgical field is increased and the lesions are more intimately associated with critical neurovascular structures.…”
Section: Learning Curve In Craniopharyngioma Surgerymentioning
confidence: 99%
“…In fact, very little published documentation exists regarding the learning curve associated with endonasal cranial base cases in general. 17,18,24,30,33 The purpose of the present study was to determine if, and to what extent, a learning curve exists for the endoscopic transnasal resection of craniopharyngiomas.…”
mentioning
confidence: 99%
“…19,26 Although the benefits of the endoscopic technique for properly selected patients are clear, neurosurgeons have been slow to adopt it because of the steep operator's learning curve. 20,34,40 To that end, we present this technical descriptive report and detailed illustrations of the technical nuances recommended for endonasal endoscopic resection of craniopharyngiomas.…”
mentioning
confidence: 99%
“…13,20,25 To flatten the learning curve and clarify some of the technical nuances involved in successful removal of tuberculum sellae meningiomas, we present a purely technical descriptive study and provide elaborate illustrations prepared through 3D graphic models. The purpose of this report is to familiarize the novice endonasal surgeon with a 6-step process for removing these meningiomas.…”
mentioning
confidence: 99%
“…7 As demonstrated by the higher complication rates reported for those early in their endoscopic neurosurgical careers, the learning curve can be steep, particularly for neurosurgeons not well trained in endonasal endoscopy. 13,20,25 To flatten the learning curve and clarify some of the technical nuances involved in successful removal of tuberculum sellae meningiomas, we present a purely technical descriptive study and provide elaborate illustrations prepared through 3D graphic models. The purpose of this report is to familiarize the novice endonasal surgeon with a 6-step process for removing these meningiomas.…”
mentioning
confidence: 99%